The role of the dipole moment orientations in the crystallization tendency of the van der Waals liquids – molecular dynamics simulations - Koperwas, Kajetan (Sci Rep, 2020)
Computer simulations of model systems play a remarkable role in the contemporary studies of structural, dynamic and thermodynamic properties of supercooled liquids. However, the commonly employed model systems, i.e., simple-liquids, do not reflect the internal features of the real molecules, e.g., structural anisotropy and spatial distribution of charges, which might be crucial for the behavior of real materials. In this paper, we use the new model molecules of simple but anisotropic structure, to studies the effect of dipole moment orientation on the crystallization tendency. Our results indicate that proper orientation of the dipole moment could totally change the stability behavior of the system. Consequently, the exchange of a single atom within the molecule causing the change of dipole moment orientation might be crucial for controlling the crystallization tendency. Moreover, employing the classical nucleation theory, we explain the reason for this behavior.